Measurement of gas holdup and mass transfer in a bubble column by using electrical resistance tomography (ERT) - Nur Tantiyani Ali Othman; Nur Syamimi Wahid (Penerbit Universiti Kebangsaan Malaysia, 2017)
Gas dispersion performance and gas hold-up in a bubble column was investigated by using electrical resistance tomography (ERT). Experiments were carried out to visualize flow pattern and gas hold-up at different gas velocity, type of impeller and speed of impeller. In this study, cylindrical bubble-column with a diameter of 13.5 cm and a height of 97.5 cm, made of glass that was mounted with four planes of 16 stainless steel electrodes are connected to an ITS P2000 ERT system. The column was equipped with perforated plate consisting of five holes and each has internal diameter of 3.0 mm. The effect of four parameters; gas flowrate, speed of impeller, 2 types of impeller; Rushton and Lightnin impeller, and three types of gas; oxygen, hydrogen and nitrogen gas on the gas dispersion performance in the bubble column were investigated. It was observed that the gas dispersion rate is increased with increasing gas density where the oxygen gas has the highest of dispersion gas rate as compared to the others gas. The gas hold-up was determined from the correlation method to estimate the transition velocity and dispersion of gas in a bubble column. The results showed that with increasing of the superficial gas velocity, the total gas hold-up increases. Besides, the gas hold-up increased due to decreasing of gas density. It can be concluding that the optimum mixing condition was obtained by using Lightnin A320 impeller with the speed rate at 250 rpm.